Appropriate complementary feeding practices and associated factors among mothers with infants aged 6–8 months in West Gojjam Zone, Northwest Ethiopia: A mixed methods study - Shiferaw Birhanu; Getu Degu Alene; Yeshalem Mulugeta Demilew (PLoS ONE, 2025)
Background Appropriate complementary feeding is critical to improve children’s nutrition, health, and development. However, these practices are notably low among Ethiopian mothers. Therefore, this study aimed to assess appropriate complementary feeding practices and associated factors among mothers with infants aged 6–8 months in West Gojjam Zone, Northwest Ethiopia. Methods A community-based cross-sectional study including 802 mothers with infants aged 6–8 months was conducted from June to December 2023. Study participants were selected using a cluster sampling technique. Quantitative data were collected using structured questionnaires, while semi-structured interview guides were employed for qualitative data collection. Multivariable logistic regression was used to identify factors associated with appropriate complementary feeding practices. A p-value <0.05 was considered statistically significant. Qualitative data were thematically analyzed using Open Code 4.03 software. Results The prevalence rate of appropriate complementary feeding practices among mothers with infants aged 6–8 months was only 9.6% (0.096; 95% CI: 0.077, 0.119). A month increase in the infant’s age [AOR = 2.92, 95% CI: (1.99, 4.29)], postnatal counseling on complementary feeding [AOR = 2.64, 95% CI: (1.46, 4.75)], feeding animal-source foods on fasting days [AOR = 2.60, 95% CI: (1.20, 5.66)], higher household wealth: being rich [AOR = 3.13, 95% CI: (1.32, 7.40)], and richest [AOR = 3.16, 95% CI: (1.34, 7.49)], and perceived susceptibility [AOR = 2.45, 95% CI: (1.39, 4.31)] were predictors of appropriate complementary feeding practices. Additionally, excessive workload, misconceptions, and poverty were barriers to these practices. Conclusion Most mothers in this study practiced inappropriate complementary feeding. Therefore, healthcare providers should strengthen postnatal counseling on complementary feeding and promote provision of age-appropriate animal-source foods on fasting days. Improving households’ economic status and mothers’ understanding of the risks associated with inappropriate complementary feeding practices is crucial. Collaboration among stakeholders, including women’s affairs and religious leaders, can help reduce mothers’ workload and address misconceptions about complementary feeding practices.